A new species of the genus Crossodonthina (Collembola: Neanuridae: Lobellini) from China - Luo, Yongzheng; Chen, Jian-Xiu (Zootaxa, 2009)
The genus Crossodonthina Yosii, 1954 is briefly introduced and a new Chinese species, Crossodonthina bidentata, from Zhejiang Province, is described in the present paper. It is distinguished from all known members of the genus by two unique characters: tubercles Di fused on Abd. V and the unique structure of the mandibles and maxillae. Its labral chaetotaxy (2/5, 2), setae on furcular remnant and morphology of macrosetae (M) are also unusual for the genus. It is similar to the Chinese species, C. montana Lee & Kim, 1990 and C. hainana Xiong et al., 2005, in having 2+2 eyes, 8 sensory setae on Ant. IV, 1 inner tooth on unguis, 4+4 setae on ventral tube and in the body dorsal chaetotaxy. However, it differs from them in the setae on cephalic tubercles Oc, setae on furcular remnant and the morphological feature of macrosetae (M), as well as the fusion of Di tubercles on Abd. V and the structure of mandibles and maxillae. A key to world species of the genus is provided.